ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TERJADINYA KEJAHATAN SEKSUAL OLEH PELAKU ANAK - Asmawati, Hermi (CV. Era Digital Nusantara, 2022)
The purpose of this research is to analyze what factors can influence the occurrence of sexual crimes against children. This study uses a qualitative research method with a phenomenological descriptive approach, namely understanding a phenomenon related to the factors that influence the occurrence of sexual violence in adolescents. In this study, an analysis was carried out regarding the phenomenon using concepts and theories based on references that were relevant to the research theme, namely related to sexual crimes committed by children. The results of the study concluded that there were two factors that could influence the occurrence of sexual crimes by children as perpetrators, namely the group of intrinsic motivation factors including intelligence factors, age factors, gender factors, and factors of the child's position in the family and groups of intrinsic motivation factors including family factors and educational factors.